2021
DOI: 10.3390/agriculture11020175
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emission and Milk Production from Jersey Cows Grazing Perennial Ryegrass–White Clover and Multispecies Forage Mixtures

Abstract: Methane is a major constituent of greenhouse gas (GHG) emissions from ruminants, and mitigation strategies are needed to alleviate this negative environmental impact while maintaining the environmental and other benefits of grazing systems. Forages containing plant-specialized metabolites (PSM), particularly condensed tannins, may help reduce enteric methane (CH4) emissions. However, information on in vivo CH4 emissions from cows grazing mixtures that contain bioactive herbs is scarce. Accordingly, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
3
22
0
1
Order By: Relevance
“…The main advantages of an IFG is the possibility of the inclusion of leys in a cash-crop arable system to accelerate C and N accumulation in the soil as a result of BNF from grass-clover leys and animal-N excreta; and in terms of forage provision the benefits of continuous progress in forage plant breeding, as expressed as high energy and protein values similar to concentrate feed, can be gained by frequent renovation of the seeded leys. Moreover, leys offer the opportunity to include alternative species such as forage herbs that may benefit the digestibility and forage intake of grazing animals (Loza et al, 2021) at low N 2 O emissions from pasture land (Nyameasem et al, 2021). Lorenz et al (2019), moreover, noticed that the efficiency of the proposed dairy systems depends on the farm management and that the evaluation of such systems needs accurate estimates of the forage efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of an IFG is the possibility of the inclusion of leys in a cash-crop arable system to accelerate C and N accumulation in the soil as a result of BNF from grass-clover leys and animal-N excreta; and in terms of forage provision the benefits of continuous progress in forage plant breeding, as expressed as high energy and protein values similar to concentrate feed, can be gained by frequent renovation of the seeded leys. Moreover, leys offer the opportunity to include alternative species such as forage herbs that may benefit the digestibility and forage intake of grazing animals (Loza et al, 2021) at low N 2 O emissions from pasture land (Nyameasem et al, 2021). Lorenz et al (2019), moreover, noticed that the efficiency of the proposed dairy systems depends on the farm management and that the evaluation of such systems needs accurate estimates of the forage efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Nyameasem et al [34], on the same experimental site, reported low levels of N 2 O emissions which further indicates the effective use of N in the low-input system [20]. With regard to the N on a farm-level, a low-input ley-systems based on grazing allows for high productivity in combination with high biodiversity effects [68], low GHG emissions [16,34] and milk production with a low carbon footprint, thereby resulting in eco-efficient dairy systems [69]. These low-input systems could therefore serve as a platform in order to reduce the negative environmental effects associated with dairy farming in northern Germany which will adhere to the European Union Nitrate Directive [8], the Water Framework Directive [9] and the Groundwater Directive [10], organizations that aim to protect both surface and groundwater from agricultural use.…”
Section: Field-n-balancementioning
confidence: 85%
“…The inclusion of forage herbs in grass-clover swards has been found to encourage a reduction in the environmental impact of milk production [14]. Several other publications support this statement and indicate that the inclusion of legumes and forage herbs in pastures can reduce the impact of milk on the environment [6,15,16]. Forage crops in mixed farming systems, also referred to as ley-arable-systems, have traditionally been used in Europe as an additional source of feed for ruminants.…”
Section: Introductionmentioning
confidence: 97%
“…The study took place in 2019 at the Lindhof experimental farm of Kiel University, in Schleswig-Holstein, Germany (WGS 84, 54 • 28 N; 9 • 58 E), in the frame of the topic "Eco-efficiency of pasture-based milk production" [54][55][56]. In 2019, the mean temperature of the study area was 10.24 • C (mean annual temperature of 9.35 • C between 1990 and 2019) and the annual precipitation was 745 mm (mean annual precipitation of 775 mm between 1990 and 2019).…”
Section: Study Region and Designmentioning
confidence: 99%